Immunological studies in a case of T-cell leukaemia. Issue 11 (November 1974) - Stathopoulos, G.; Papamichail, M.; Sheldon, P.; Catovsky, D.; Davies, A. J. S.; Holborow, E. J.; Wiltshaw, Eve
Abstract : The blood lymphocytes from a case of prolymphocytic leukaemia were subjected to a battery of different tests in order to establish as certainly as possible their T or B cell type of origin. The results of the tests for surface markers indicated the T-cell origin of the leukaemic cells in this patient, and this provided a good opportunity to determine the participation of T cells in the various tests proposed for measuring human lymphocyte function.